Pengaruh Nisbah Bagi Hasil dan Kualitas Pelayanan Pada Produk Tabungan IB Hidayah Terhadap Loyalitas Nasabah: (Studi Pada Bank Pembiayaan Rakyat Syariah Bangka Belitung Cabang Pangkalpinang) - Musa, Musa (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2019)
The presence of BPR Syariah Bangka Belitung Branch of Pangkalpinang as one of the banks that applies a profit sharing system, so that it raises the desire and loyalty of customers to transact at Islamic banks. In addition, BPR Syariah is required to provide quality service with maximum service standards. This is as a bank’s accountability to be to compete with other banks in increasing customer loyalty. The main problem in this study: How is the effect of profit sharing ratio and quality of service on iB Hidayah savings products on customer loyalty BPR Syariah Bangka Belitung Branch Pangkalpinang. While the aim is to analyze the effect of profit sharing ratios and service quality on iB hidayah savings products on customer loyalty of BPR Syariah Bangka Belitung Branch of Pangkalpinang.  The type of this research is descriptive-quantitative. This means that the type of research that produces findings with a statistical step. Furthermore, the sampling rechnique of this study used a simple ramdom sampling rechnique. While the data collection techniques used are observation, questionnaires, and documentation. The data analysis technique used is the instrument test, classic assumption test, multiple linear regression test, and hypohtesis testing. This research uses SPSS Version 22.0 software.The results of this study incicate that: (1) Variable ratio of profit sharing and service quality in the coefficient of determination has the effect of contributing to customer loyalty in iB Hidayah savings products at BPR Syariah Bangka Belitung Branch Pangkalpinang by 61,7%. While the remaining 38,3% is influenced by other variables not examined. (2) Variable ratio of profit sharing and service quality simultaneously influences customer loyalty on iB hidayah savings products at BPR Syariah Bangka Belitung Branch Pangkalpinang. Can be indicated by the value of Fcount 74,225 > Ftable 3,10 with a significance level of 0,000 < 0,05. (3) Variable ratio of profit sharing and service quality partially influences customer loyalty on iB hidayah savings products at BPR Syariah Bangka Belitung Branch Pangkalpinang. Ii can be shown by the tcount values respectively 5,956 and 5, 584 > ttable 1,98609 with a significance level respectively 0,000 < 0,05.